High-resolution aquifer analog of fluvial-aeolian sediments of the Guarani aquifer system - Höyng, Dominik; D'Affonseca, Fernando Mazo; Bayer, Peter; de Oliveira, Edson Gomes [UNESP]; Perinotto, José Alexandre de Jesus [UNESP]; Reis, Fábio [UNESP]; Weiß, Holger; Grathwohl, Peter (Springer Nature, 2013)
The Guarani aquifer system (GAS) represents one of the biggest aquifers in the world and is the most relevant groundwater resource in South America. For the first time, by combining field and laboratory measurements, a high-resolution aquifer analog model of fluvial-aeolian sediments of the GAS in São Paulo State (Brazil) is constructed. Three parallel sections of frontal outcrops, 28 m × 5.8 m, and two parallel sections of lateral outcrops, 7 m × 5.8 m, are recorded during open-pit mining of sandy sediments and describe in detail the three-dimensional distribution of the local lithofacies and hydrofacies. Variations of hydraulic conductivity, K, and porosity, n, are resolved on the centimeter scale, and the most permeable units of the fluvial-aeolian facies association are identified. The constructed aquifer analog model shows moderate hydraulic heterogeneity and a mean K value of 1.36 × 10-4 m/s, which is greater than the reported range of K values for the entire GAS in São Paulo State. The results suggest that the examined sedimentary unit constitutes a relevant portion of the GAS in São Paulo State in the context of groundwater extraction and pollution. Moreover, the constructed aquifer analog is considered an ideal basis for future numerical model experiments, aiming at in-depth understanding of the groundwater flow and contaminant transport patterns at this GAS portion or at comparable fluvial-aeolian facies associations. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Fluvial-aeolian sediments; Groundwater reservoir analog model; Guarani aquifer; Pirambóia Formation; Reservoir characterization